2009
DOI: 10.1590/s1807-59322009000300012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiopulmonary Bypass on Propofol Pharmacokinetics and Bispectral Index During Coronary Surgery

Abstract: Barbosa RAG, Santos SRCJ, White PF, Pereira VA, Silva Filho CR, Malbouisson LMS. Effects of cardiopulmonary bypass on propofol pharmacokinetics and bispectral index during coronary surgery. Clinics. 2009;64(3):215-21. PURPOSE:Cardiopulmonary bypass is known to alter propofol pharmacokinetics in patients undergoing cardiac surgery. However, few studies have evaluated the impact of these alterations on postoperative pharmacodynamics. This study was designed to test the hypothesis that changes in propofol pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…22 Barbosa et al reported pharmacokinetics of propofol modified by the CPB, may contribute to an increase in hypnotic effects after cardiac surgery. 23 In our clinical practice, fentanyl and dormicum infusion continued to be administrated during the CPB and we speculate that the effects of the CPB on these anesthetic drugs may be related to our finding.…”
Section: Discussionsupporting
confidence: 53%
“…22 Barbosa et al reported pharmacokinetics of propofol modified by the CPB, may contribute to an increase in hypnotic effects after cardiac surgery. 23 In our clinical practice, fentanyl and dormicum infusion continued to be administrated during the CPB and we speculate that the effects of the CPB on these anesthetic drugs may be related to our finding.…”
Section: Discussionsupporting
confidence: 53%
“…43 Furthermore, the unbound propofol fraction increases during CPB, which might decrease the blood propofol concentration required to maintain anesthesia during CPB. 44 Closed-loop anesthesia using BIS during cardiac surgery has been shown to decrease propofol administration and to increase hemodynamic stability compared to dosing controlled manually by anesthesiologists based upon the BIS reading.…”
Section: Anesthetic Dosingmentioning
confidence: 99%
“…42 Apart from altering pharmacokinetics, CPB is hypothesized to increase the sensitivity of the brain to anesthesia. 43 Furthermore, the unbound propofol fraction increases during CPB, which might decrease the blood propofol concentration required to maintain anesthesia during CPB. 44 Closed-loop anesthesia using BIS during cardiac surgery has been shown to decrease propofol administration and to increase hemodynamic stability compared to dosing controlled manually by anesthesiologists based upon the BIS reading.…”
Section: Anesthetic Dosingmentioning
confidence: 99%